2023
DOI: 10.1155/2023/8622745
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Alpinia oxyphylla Fructus Polysaccharides Extracted with Different Solvents on Dextran Sulfate Sodium-Induced Ulcerative Colitis in Mice

Xinyue Ma,
Liyan Li,
Dezhi Deng
et al.

Abstract: Ulcerative colitis (UC) is a temporary incurable inflammatory bowel disease. Alpinia oxyphylla fructus polysaccharides (AOFPs) have anti-inflammatory, antioxidant, and other biological activities. In order to explore the therapeutic effect of AOFPs on UC, this study used deionized water, NaCl, HCl, and NaOH to extract AOFPs, and their protective effects on UC were evaluated by dextran sulfate sodium-induced UC mouse model. The results showed that extraction solvents had significant effects on the yield, molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Yang et al characterized the structure of A. oxyphyllae fructus polysaccharide and found that it could significantly increase the phagocytic activity of RAW264.7 macrophages [ 9 ]. Generally, the bioactivity of polysaccharides depends on the chemical composition and structural features, which varies with a range of factors, especially the extraction solvent employed [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al characterized the structure of A. oxyphyllae fructus polysaccharide and found that it could significantly increase the phagocytic activity of RAW264.7 macrophages [ 9 ]. Generally, the bioactivity of polysaccharides depends on the chemical composition and structural features, which varies with a range of factors, especially the extraction solvent employed [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%